Analysis of Students' Science Literacy Ability on Heat Concept - Anderias Henukh; Merta Simbolon; I Made Astra; Haris Rosdianto (STKIP Singkawang, 2021)
This study aims to describe the scientific literacy skills of students where the results can be used as a basis for implementing learning with the STEM approach based on local wisdom of Papua. This research was conducted at SMP YPPK St. Mikael Merauke in class VIII SMP students, especially in the heated material. This research uses a descriptive quantitative method. The instrument used in this study was multiple-choice totaling 30 numbers based on scientific literacy. The research instrument used has gone through a validation process and is declared valid. The results of the data analysis showed that the scientific literacy skills of students on the indicator of understanding scientific phenomena obtained an average score of 66%. The indicator explaining scientific phenomena obtains an average score of 62%. In the scientific problem identification indicator, the average score obtained is 65%. However, on the indicators of interpreting the data and scientific evidence the average score obtained was 59%. In the domain of scientific literacy, the aspect of scientific knowledge obtained an average score of 66%. Likewise in the scientific competency aspect, the average score obtained is 62%. Based on the results of the data analysis, it can be concluded that the overall score of students' scientific literacy skills is in a good category.